ترقية التفكير الإبداعي والنقدي في مهارة الكلام العربي بوسيلة بودكاست في المدرسة: Enhancing Creative and Critical Thinking in Arabic Speaking Skills through Podcasts in Schools - Shobirin Shobirin; Niswatush Sholihah; Ishlahuddin Ishlahuddin; Uril Baharuddin (Journal of Arabic Language Teaching, 2025)
Using podcasts to teach speaking skills can significantly enhance students' critical and creative thinking abilities. Podcasts also promote greater linguistic interaction, which helps students improve their pronunciation and understanding of Arabic kalam. However, teachers often face challenges, such as limited training or lack of experience using this method. This qualitative research explores how podcast integration contributes to developing speaking skills and thinking abilities among Zainul Hasan Genggong Model High School students. Data were collected through interviews, observations, and documentation. Semi-structured interviews with teachers and students revealed their experiences, opinions, and challenges in using podcasts as a learning tool. Observations were conducted during lessons involving podcasts, focusing on student engagement, participation, and speaking improvement. Supporting documentation included lesson plans, activity notes, podcast recordings, and speech assessments. Data were analyzed thematically, involving coding and identifying recurring themes. Triangulation of sources and methods was used to ensure credibility. The podcast implementation process involved planning, execution, and evaluation. Teachers also received phased training—starting with basic tools, followed by hands-on practice, and ongoing support. With their interactive, creative, and collaborative nature, podcasts offer valuable opportunities to foster students' speaking proficiency and stimulate their critical and innovative thinking.